Interleukin 18 in the CNS - Sugama Shuei; Cervia Davide; Alboni Silvia; Conti Bruno (Journal of Neuroinflammation, 2010)
Abstract Interleukin (IL)-18 is a cytokine isolated as an important modulator of immune responses and subsequently shown to be pleiotropic. IL-18 and its receptors are expressed in the central nervous system (CNS) where they participate in neuroinflammatory/neurodegenerative processes but also influence homeostasis and behavior. Work on IL-18 null mice, the localization of the IL-18 receptor complex in neurons and the neuronal expression of decoy isoforms of the receptor subunits are beginning to reveal the complexity and the significance of the IL-18 system in the CNS. This review summarizes current knowledge on the central role of IL-18 in health and disease.